The Alignment of Business and Information Technology Strategy in Australia - Gartlan, Jovita; Shanks, Graeme (Australasian Journal of Information Systems, 2007)
The alignment of business and information technology strategy has long been recognised as a key issue for managers and has grown in importance as IT has become strategically significant. Previous studies have noted the elusiveness of alignment of business and information technology strategy and identified a number of factors that promote alignment. This study builds on previous work and categorises the factors as either people, process or organisational. A cross industry survey of Australian organisations is then used to determine the perceived benefits of alignment and the perceived importance of each factor and how successful it was in promoting alignment. The findings of the study show that Australian organisations perceive that alignment is important and can bring considerable benefits. Furthermore the study highlights the relative importance of the factors and indicates where organisations should focus their attention in order to successfully achieve alignment.